Embranquecimento do candomblé? uma análise da linha sucessória do Axé Ilê Obá, terreiro de tradição Queto na região do Jabaquara, São Paulo - Bonine, Eduardo (2020)
The main purpose of this work is to analyze the succession line of Axé Ilê Obá, a Candomblé Queto terreiro (of Queto nation), in the Jabaquara region, south zone of the city of São Paulo, focusing on the third and current generation of home, in order to identify a supposed process of whitening candomblé. The development of the research takes place between the walls of the house, in order to collect the memories in the narratives of the sons and daughters of the saint. The work proposes to investigate, through a decolonial approach, the social and cultural reasons that possibly led a religion that was born in the hands of the black population to “whiten”, over the last three decades